MADRASAH INFRASTRUCTURE MANAGEMENT BEFORE FACE-TO-FACE LEARNING IN THE PANDEMIC - Sundaniawati Safitri; Sri Mulyati; Wahyudi Wahyudi; Maftuhah Maftuhah; Zahruddin Zahruddin (JURNAL AL-TANZIM, 2021)
This current study aimed to analyze and comprehend the management of the madrasa's facilities and infrastructure to hold face-to-face learning during the Covid-19 pandemic. This study was conducted at MI Soebono Mantofani, which is located in Ciputat, South Tangerang. The study employed a descriptive approach with qualitative methods. Data were obtained through interviews, observation, and documentation. The data analysis technique in this study followed the procedures: data reduction, data presentation, conclusion drawing, and verification. The study results highlighted the importance of needs analysis before preparing facilities and infrastructure planning policy to procure facilities and infrastructure by available safety procedures. Besides, the school management system also endorsed the principal's critical role in preparing the recipes, organizing the facilities during face-to-face learning, and holding the maintenance process accountable. This study also provided implications for managing the facilities and infrastructure amidst pandemics and hopefully shed some light on other relevant stakeholders in facing the upcoming face-to-face learning in the middle of the pandemic.